Caseworker prejudice: exploring secondary non-take-up from below among Latino immigrants in Madrid, London, and New York City - Mallet, M; Garcia, E (Sciendo, 2021)
This article investigates the understudied phenomenon of secondary non-take-up (NTU) among Latino immigrants in Madrid, London, and New York City from their own perspective. It examines the reasons behind secondary NTU across the three sites and examines the relevance of type of welfare state in which they live. The findings of this paper suggest that secondary NTU is prevalent in these three sites. It identifies prejudice from social workers as the leading cause of secondary NTU among Latino immigrants.